Descriptive evaluation of 181 children with supracondylar humerus fractures, Hospital Universitario del Valle. Cali, Colombia, 1983-1987 (Colombia Medica, 1989)
A retrospective study of 5 years of supracondylar fractures of the humerus in children was done at the Hospital Universitario del Valle, Cali, Colombia; 181 cases were evaluated, and it was found most frequent in boys (71%) between 5 to 8 years of age. The cause of fracture most frequently was falling down during playing games.Closed fracture was present in 81% of the cases, and neurological lesions were present in 12.2%, from which equal frequency was found in the median and radial nerves. Those patients with displaced fractures type III treated with closed reduction and Velpeau cast, the most common complication was displacement. Volkman contracture was not found in any case.